2008
DOI: 10.2174/1874155x00802010128
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Relative Humidity and Roughness on the Friction Coefficient under Horizontal Vibration

Abstract: The present paper investigates experimentally the effect of relative humidity and roughness on friction property of mild steel under horizontal vibration. To do so, a pin-on-disc apparatus having facility of vibrating the test samples at different direction is designed and fabricated. The direction of vibration is horizontal. Horizontal vibration is created along (longitudinal direction) and perpendicular (transverse direction) to the sliding direction. The experimental setup has the facility to vary the ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Wieleba [15] had studied roughness and stiffness of composite materials against steel and showed its effect on the friction and wear. Chowdhury and Maksud [16] have searched the effect of humidity on surface roughness and found that the friction is very high at low roughness and tends to be increased at high horizontal vibration. Al-Si alloys have been studied interestingly, but did not take into consideration the roughness study.…”
Section: Introductionmentioning
confidence: 99%
“…Wieleba [15] had studied roughness and stiffness of composite materials against steel and showed its effect on the friction and wear. Chowdhury and Maksud [16] have searched the effect of humidity on surface roughness and found that the friction is very high at low roughness and tends to be increased at high horizontal vibration. Al-Si alloys have been studied interestingly, but did not take into consideration the roughness study.…”
Section: Introductionmentioning
confidence: 99%
“…A well-known friction phenomenon of audible nature, including chatter and squeal, can take place in stern bearings during start-up, shut-down, running with heavy load, low speed, high temperature and other special conditions. This phenomenon is mainly induced by stick/slip which is in connection with the tribological property of mating pair, such as negative slope of friction-velocity relation [16,17]. The purpose of this work described in this manuscript was to reveal the tribological property of the new polymer blend for stern bearing inner facing material, with comparison to a nitrile-butadiene rubber (NBR) that used for most marine ship stern bearing, especially at the speed less than 2.0m/s.…”
Section: Introductionmentioning
confidence: 99%
“…Those would allow to get better evidence of chaotic behaviour and to develop enhanced analysis techniques for noise generation. Abdo et al [58] and Chowdhury et al [59] included the effect of humidity and the frequency of vibration on the amplitude of the stick-slip vibration. It was found that as the frequency increases, the amplitude of the vibrations decreases.…”
Section: Frictionmentioning
confidence: 99%